Desempenho do eletrocardiograma no diagnóstico da hipertrofia ventricular esquerda em hipertensos idosos e muito idosos - Povoa, Fernando Focaccia [UNIFESP] (2021)
Background: Hypertension is the main cause of cardiovascular diseases in the world. In this scenario, left ventricular hypertrophy (LVH) is the most ominous manifestation. Despite the technological evolution of imaging tests, the electrocardiogram (ECG) is still the most used in the initial evaluation of these patients, despite being relatively low sensibility. Objective: to evaluate the performance of the main electrocardiographic criteria for LVH in the condition of elderly and very elderly hypertensive patients. Methods: In a cohort of hypertensive patients followed at the UNIFESP Hypertension Center. Eletrocardiogram and echocardiogram (ECO) were performed. LVH was identified by ECO by means of a left ventricular mass index > 95 g/m2 in women and > 115 g/m2 in men. Patients were shared into three age groups: <60 years, Group I; 60-79 years, Group II and ≥80 years, Group III. The electrocardiographic criteria most used in clinical practice were criteria for the diagnosis of LVH: Perugia, Peguero-Lo Presti, Gubner-Ungerleider, Narita, (Rm + Sm) QRS duration, Cornell voltage, Cornell voltage duration, Sokolow-Lyon voltage, RaVL ≥ 11 mm, and RaVL duration. In assessing the performance of these criteria, in addition to sensitivity (Sen) and specificity (Esp), we analyzed the Diagnostic odds ratio (DOR). Results: In 2.458 patients, 753 men and 1705 women, LVH was present by ECO in 781 (31.7%). In Group I and II, the best performances were for the Narita, Perugia, (Rm + Sm) duration criteria, with no differences between them. In Group III, the Perugia and (Rm + Sm) duration criteria had the best performances. In this group of very elderly patients, the Perugia criteria (44.7/89.3; sen/esp) and (Rm + Sm) QRS duration (39.4% 91.3%; sen/esp) were the best (p < 0.05), including the highest DOR results (6.8). It is necessary for this population of hypertensive patients that these criteria have greater discriminatory power to separate patients with or without LVH. Conclusion: Our data suggested that in elderly hypertensive patients, aged 60-79 years, the best electrocardiographic criteria for the diagnosis of LVH was Narita, with sensitivity (38.1%) and specificity (87.5%). And in the very elderly, over 80 years old, the Perugia and (Rm + Sm) x duration criteria presented the best performances, with Sen of 44.7% and 39.4% and Esp of 89.3% and 91.3 %, respectively.